Analysis of Revenue Recognition Based on PSAK 72 at Graha Kardopa Hotel to Support SDG 16 Transparency - Lailan Syakira Taufan; Yanni Samri Juliati Nasution; Tuti Anggraini (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the implementation of PSAK 72 concerning Revenue from Contracts with Customers at Hotel Graha Kardopa and to examine its implications for financial transparency in relation to SDG 16. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with five key informants involved in the hotel’s financial and operational processes, as well as documentation analysis of financial reports and related records. Data validity was ensured through source triangulation and document verification. The analysis focused on the implementation of the five-step revenue recognition model under PSAK 72 and transparency indicators, including accuracy, consistency, traceability, and accessibility of financial information. The findings reveal that Hotel Graha Kardopa has implemented the five-step PSAK 72 model through the integration of the cloud-based Yanolja Accounting Information System. Revenue is recognized when performance obligations are fulfilled during the guest check-out process, while revenue measurement is based on transaction prices automatically recorded in the system. The integrated system facilitates data synchronization across departments and improves the reliability of financial records. These findings suggest that the implementation of PSAK 72 contributes to enhancing financial transparency and accountability practices, which are aligned with the principles promoted under SDG 16 regarding effective, accountable, and transparent institutions.